Transitioning to Teaching Online During the COVID-19 Pandemic. (June 2021) - Wilson, Jessica L.; Hensley, Angie; Culp-Roche, Amanda; Hampton, Debra; Hardin-Fanning, Fran; Thaxton-Wiggins, Amanda
Background: During the COVID-19 pandemic many nursing educators have been required to abruptly convert to an online delivery model. Faculty need resources and support to transition face to face courses into an online format. Purpose: The purpose of this article is to highlight nursing faculty perceptions of the effectiveness of resources, support, and methodologies for online teaching during the COVID-19 Pandemic. Methods: A cross-sectional descriptive survey design was used to collect data about nursing faculty resources, support and methodologies used to transition at least one undergraduate or graduate degree nursing course to an online format during the COVID-19 pandemic. Results: Eighty-four faculty who taught in ten university colleges of nursing used varied teaching methodologies in online courses, but included some consistent methods such as websites and web based tools. The student engagement strategies that faculty were most satisfied with were journal writing and projects. Most faculty reported having information technology support and access to instructional design resources. Conclusion: Nursing faculty were resourceful, adaptive, and willing to use both novel and existing resources and methodologies to meet their teaching objectives and engage students. They were also, overall, satisfied with the administrative support they received from their respective institutions. Many of these resources, methodologies, and supports will continue to be used by faculty as likely more programs and courses will continue to be managed online.